A new computational approach to the study of epitaxy: the calcite/dolomite case. Issue 28 (3rd July 2017) - Bruno, M.; Massaro, F. R.; Rubbo, M.
Abstract : A new way to determine the adhesion and interfacial energies in epitaxial systems is presented. Abstract : A new way to analyze the theoretical and computational aspects related to the determination of the adhesion and interfacial energies in epitaxial systems is presented. Then, we studied the epitaxial phenomena in calcite (Cc)–dolomite (Dol) systems by adopting the recent computational strategy designed by our research group. Specifically, we investigated at the empirical level the (10.4)Cc/(10.4)Dol, (10.0)Cc/(10.0)Dol and (11.0)Cc/(11.0)Dol epitaxial interfaces determining their structures and thermodynamic properties. Moreover, we showed how energy distribution is modified in the layers of calcite and dolomite at the epitaxial interface. These results are used to gain some insights into the epitaxial growth of dolomite above calcite. In particular, we found that the (10.0)Cc/(10.0)Dol interface shows minor structural modifications, as well as the highest adhesion energy. This implies that the probability to have epitaxy between calcite and dolomite is higher for the (10.0)Cc/(10.0)Dol interface with respect to that of (11.0)Cc/(11.0)Dol and (10.4)Cc/(10.4)Dol.